2004
DOI: 10.1103/physrevb.70.195340
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine interaction in a quantum dot: Non-Markovian electron spin dynamics

Abstract: We have performed a systematic calculation for the non-Markovian dynamics of a localized electron spin interacting with an environment of nuclear spins via the Fermi contact hyperfine interaction. This work applies to an electron in the s-type orbital ground state of a quantum dot or bound to a donor impurity, and is valid for arbitrary polarization p of the nuclear spin system, and arbitrary nuclear spin I in high magnetic fields. In the limit of p = 1 and I = 1 2 , the Born approximation of our perturbative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
768
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 454 publications
(788 citation statements)
references
References 48 publications
18
768
1
1
Order By: Relevance
“…72,73,79 There are also numerous non-Markovian generalizations of the master equation. [80][81][82][83] In the above derivation it was assumed that the system is weakly coupled to the environment. Indeed, for practical purposes this is the most interesting case: if the coupling of the system to the environment is strong, the system behaves classically and can be described with classical equations of motion, while if the coupling is absent altogether, eqn (1) is valid.…”
Section: This Journal Is C the Owner Societies 2010mentioning
confidence: 99%
“…72,73,79 There are also numerous non-Markovian generalizations of the master equation. [80][81][82][83] In the above derivation it was assumed that the system is weakly coupled to the environment. Indeed, for practical purposes this is the most interesting case: if the coupling of the system to the environment is strong, the system behaves classically and can be described with classical equations of motion, while if the coupling is absent altogether, eqn (1) is valid.…”
Section: This Journal Is C the Owner Societies 2010mentioning
confidence: 99%
“…Consequently, it has been reported that (inhomogeneous) electron spin-dephasing times of T * 2 = 0.5 − 6 μs can be achieved in Diamond, at 300 K-without the need for cryogenic cooling [1,4,18], which makes Diamond an attractive candidate for Quantum Information Processing. Following [12], however, we argue that whilst it is clear that a successful qubit can be constructed from the spin polarization the 3 A 2 state (as has been successfully demonstrated in [1,4,9,16,17]) it is not at all clear why this state should be so highly stable from a calculational standpoint, with such a relatively long decoherence time, given the current understanding of the mechanism of spectral diffusion [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is our new argument that this qubit does not simply decohere to become entangled with the bath, but with a bath which is also decohering to become entangled with itself and, therefore, that this slowly changes the definition of the SO(3) rotational symmetry of the electron spin to make it evolve into an oblate spheroid (relative to its initial spin projection). Whilst previous calculational schemes have treated the nuclear spin bath dynamics [19,20], these schemes have been restricted to short-time regimes and localised electron states, which we are now able to go beyond in our new approach. The limitation we have resolved is that there is generally a two-scale process involved in bath dynamics: The range of the nuclear dipole interaction strength and the cluster size of the frozen cores of nuclear spins that form through the flip-flop processes [19], and it was not previously understood to be possible to define a expansion program that is simultaneously valid at two very different scales.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations